1959
DOI: 10.1037/h0049234
|View full text |Cite
|
Sign up to set email alerts
|

Short-term retention of individual verbal items.

Abstract: The 9 lives of short-term memory. In A. Thorn & M. Page (Eds.), Interactions between short-term and long-term memory in the verbal domain (pp. 16 -43). Hove, UK: Psychology Press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
1,459
8
42

Year Published

1966
1966
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,689 publications
(1,553 citation statements)
references
References 10 publications
44
1,459
8
42
Order By: Relevance
“…Empirical data that fall close to the criterion are fit equally well by both models. Figure 5 displays the HY/SE landscapes for Wixted and Ebbeson's (1991) design on the left, and Peterson and Peterson's (1959) design on the right, with the empirical data (indicated by circles and triangles) overplotted. Despite the similarity between the landscapes, the empirical data behave rather differently to one another.…”
Section: Applying the Landscapes To Empirical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical data that fall close to the criterion are fit equally well by both models. Figure 5 displays the HY/SE landscapes for Wixted and Ebbeson's (1991) design on the left, and Peterson and Peterson's (1959) design on the right, with the empirical data (indicated by circles and triangles) overplotted. Despite the similarity between the landscapes, the empirical data behave rather differently to one another.…”
Section: Applying the Landscapes To Empirical Datamentioning
confidence: 99%
“…The data on the left are from Wixted and Ebbeson (1991). The data on the right are from Peterson and Peterson (1959).…”
Section: Applying the Landscapes To Empirical Datamentioning
confidence: 99%
“…Consider, for example, some very different attempts to state the duration of STM. Early investigators of human STM (Brown 1958, Peterson & Peterson 1959 reported that it lasts only about 30 sec if rehearsal is prevented. Agranoff et al (1966) reported that in goldfish, if formation of LTM is prevented by an inhibitor of protein synthesis, STM can last up to 3 days, although normally LTM forms within an hour after training.…”
Section: Can Parts Of the Neurochemical Cascade Be Related To Differementioning
confidence: 99%
“…Blanchard and Honig (1976), Grant, Brewster, and Stierhoff (1983), Kamin (1969), Maki (1979), and Terry and Wagner (1975) have all reported that surprising events are better remembered than expected events, presumably reflecting more extensive processing. Moreover, numerous students of human cognition (e.g., Brown, 1958;Peterson & Peterson, 1959) have argued that one event will interfere with the processing of another to the degree that the former strains the (presumably) limited processing capacity of the organism. Integrating the notion that surprise enhances processing with the view that retention can be impaired by a nontarget event that overloads a limited processing capacity, Kremer (1979) and Wagner, Rudy, and Whitlow (1973) demonstrated that an unexpected, salient intervening nontarget US presentation interfered with manifest retention of a temporally proximal target CS-US pairing more than did an otherwise comparable expected intervening event.…”
mentioning
confidence: 99%